1991
DOI: 10.1103/physrevlett.66.2665
|View full text |Cite
|
Sign up to set email alerts
|

Basic similarities among cuprate, bismuthate, organic, Chevrel-phase, and heavy-fermion superconductors shown by penetration-depth measurements

Abstract: Muon-spin-relaxation and bulk measurements of the magnetic-field penetration depth suggest that the cuprate high-7V, bismuthate, organic, Chevrel-phase, and heavy-fermion systems possibly belong to a unique group of superconductors characterized by high transition temperatures T c relative to the values of n s /m* (carrier density/effective mass). This feature distinguishes these exotic superconductors from ordinary BCS superconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
327
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 728 publications
(367 citation statements)
references
References 17 publications
38
327
1
1
Order By: Relevance
“…B) More importantly, this conclussion is supported on empirical grounds, if we use measured values of the London penetration depth to deduce T θ . Indeed, not only is T θ comparable in magnitude to T c , it often exhibits similar trends with doping and changes in other material properties, especially in the "underdoped region" where x is small; this important correlation was originally noticed by Uemura et al [4], and is called the "Uemura relation." On the otherhand, in "overdoped" materials, T θ overestimates T c by as much as a factor of three or four.…”
Section: Introductionmentioning
confidence: 93%
“…B) More importantly, this conclussion is supported on empirical grounds, if we use measured values of the London penetration depth to deduce T θ . Indeed, not only is T θ comparable in magnitude to T c , it often exhibits similar trends with doping and changes in other material properties, especially in the "underdoped region" where x is small; this important correlation was originally noticed by Uemura et al [4], and is called the "Uemura relation." On the otherhand, in "overdoped" materials, T θ overestimates T c by as much as a factor of three or four.…”
Section: Introductionmentioning
confidence: 93%
“…Originally Uemura et al [6] suggested a relation ρ s ∝ T c which works well in the case of underdoped cuprates. More recently, Homes et al [7] extended the scaling relation by an additional term covering the optimal and overdoped cuprates as well: ρ s = (125 ± 25)σ dc T c , where the σ dc is the value of dc conductivity just above T c .…”
mentioning
confidence: 99%
“…In the dirty limit where 1/[2∆ 0 τ imp (1 + λ)] ≫ 1, it is instead given by n dirty s (T = 0) = nπ∆ 0 τ imp with λ dropping out [13]. For fixed n, this gives immediately a relation between the superfluid density n s , T c , and σ n [17,18,19] The superfluid density so estimated is shown in Table I; its variation is due entirely to the change in T c . We note also the large peak at 2∆ 0 in 1 + λ op , predicted by theory and seen in the data.…”
mentioning
confidence: 99%